Prosedur Pengawasan Lalu Lintas Barang pada Kantor Pengawasan, Pelayanan Bea dan Cukai Tipe Madya Pabean C Langsa - Wiriani, Erni; Khadafi, Muhammad Ferdinan (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2022)
This study aims to determine the Procedure for Supervision of the Traffic of Goods at the Customs and Excise Supervision and Service Office of Type C Langsa Customs and to find out the obstacles in supervising the Traffic of Goods in the Langsa City Region, East Aceh Regency and Tamiang Regency by the Customs Supervision and Service Office. And Customs Intermediate Excise C Langsa. Data collection techniques used are observation, interviews, literature study and documentation. The data collected was processed and analyzed descriptively qualitatively. The research informants in this study consisted of 4 employees from the Customs and Excise Office of Middle Type Customs C Langsa and 2 people from the community. From the results of the study, it was concluded that: First, the Office of Supervision and Service of Customs and Excise Intermediate Customs Type C Langsa has carried out the procedures for controlling goods in accordance with the provisions of Customs and Excise in the Langsa City area to the maximum. However, the implementation has not been optimal because there are still factors that hinder the implementation of the supervision. Second, the size of the customs area under the authority of the KPPBC TMP C Langsa supervision area is not proportional to the number of employees or apparatus owned by KPPBC TMP C Langsa. With a total of 45 employees and officers, they have not been able to reach the specified supervision.